Pengaruh Motivasi Dan Sikap Terhadap Keputusan Pembelian Mobil Toyota Fortuner Di Kota Palembang - Putri, Frans Siska Chandra; Megawati, Megawati (Universitas Multi Data Palembang, 2024)
This research aims to determine the influence of motivation and attitudes on the decision to purchase a Toyota Fortuner car in Palembang City. The sample in this research was 194 consumers who bought a Toyota Fortuner car in Palembang City. The research method used in this research is a quantitative method. Determination of the sample using the purposive sampling method. The type of data used is primary data and the analysis method used is multiple linear regression with SPSS version 23. The results of this study show that motivation and attitude variables have a positive and significant effect on the decision to purchase a Toyota Fortuner car in Palembang City.